Pengaruh Ekuitas Merek Terhadap Keputusan Membeli Produk Kosmetik Merek Oriflame - Devi Nilakandi (Postgraduate, University of Mataram, 2020)
The purpose of this study was to determine the significance of the effect of brand equity (brand awareness, quality impression, brand association, brand loyalty) of Oriflame cosmetic products on consumer purchases in Mataram City. The population of this study are consumers who make real purchases and consumers who have tried through a demo conducted by personal selling Oriflame cosmetic products. Sampling of 50 consumers really fulfills the requirements for a representative sample. The data collection techniques used were interview techniques and documentation techniques. This analysis is used because in this study there is more than one independent variable. This analysis is used to determine the influence of brand equity (brand awareness, quality impression, brand association, and brand loyalty) on consumer purchase desires (decisions). The results showed that: 1) Brand awareness and perceived quality factors have a significant influence to form an image and influence consumer decisions in purchasing oriflame products; 2) The factors of brand association and consumer loyalty do not have a meaningful influence on purchasing decisions for Oriflame products. This means that brand association and brand loyalty are not the dominant factors that influence consumers to use Oriflame products even though these factors have an influence but the effect is small; and 3) Brand equity has a strong influence on consumer decisions in purchasing Oriflame products. This means that the stimuli attached to the oriflame product create a special attraction that attracts consumers to buy and use oriflame products.